2008
DOI: 10.1371/journal.pone.0002096
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell-Derived Histamine Mediates Cystitis Pain

Abstract: BackgroundMast cells trigger inflammation that is associated with local pain, but the mechanisms mediating pain are unclear. Interstitial cystitis (IC) is a bladder disease that causes debilitating pelvic pain of unknown origin and without consistent inflammation, but IC symptoms correlate with elevated bladder lamina propria mast cell counts. We hypothesized that mast cells mediate pelvic pain directly and examined pain behavior using a murine model that recapitulates key aspects of IC.Methods and FindingsInf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(95 citation statements)
references
References 46 publications
3
87
1
1
Order By: Relevance
“…The EvF protocol can easily be modified for use on tissues other than the hind paw e.g. abdomen 7 and ano-genital ridge 8 where CvF is currently used. Rodent models of allergies, wound healing, neuropathies and other pathologies can be easily adapted to include measures of mechanical sensitivity in tissues including and beyond the hind paw.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The EvF protocol can easily be modified for use on tissues other than the hind paw e.g. abdomen 7 and ano-genital ridge 8 where CvF is currently used. Rodent models of allergies, wound healing, neuropathies and other pathologies can be easily adapted to include measures of mechanical sensitivity in tissues including and beyond the hind paw.…”
Section: Discussionmentioning
confidence: 99%
“…Place absorbent material below the stand to absorb/collect excreted waste. Allow mice to acclimate for 15 min in chambers prior to baseline or experimental withdrawal threshold assessment 6,7,10 . 5.…”
Section: General Considerations For Hind Paw Withdrawal Threshold Assmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, pain responses mediated by histamine and histamine receptors have been described in both animal and human models (Thilagarajah et al, 2001;Mobarakeh et al, 2006). Although the specific cell type (it could be mast cells, basophils, neutrophils or dendritic cells) or histaminergic neurons regulating histamine-mediated pain have not been identified, it has been demonstrated, using a model of PRV-induced pelvic pain in mast cell-deficient Kit W-sh /Kit W-sh mice, that mast cells are required for histamine-mediated pelvic pain (Rudick et al, 2008). However, the same authors demonstrated that Kit W-sh /Kit W-sh mice reconstituted with HDC -/-bone marrow exhibited diminished pain, thus suggesting that non-mast cell sources of histamine may also contribute to this pain response.…”
Section: Histamine and Neurogenic Inflammation In The Bladdermentioning
confidence: 99%
“…However, the same authors demonstrated that Kit W-sh /Kit W-sh mice reconstituted with HDC -/-bone marrow exhibited diminished pain, thus suggesting that non-mast cell sources of histamine may also contribute to this pain response. Moreover, Rudick et al (2008) demonstrated that PRV-induced pelvic pain is not dependent on TNF-mediated effects but is mediated by mast cell hista- mine, which then induces pain by stimulating histamine H1 and H2 receptors. Thus, it has been suggested that antagonists of histamine H1 and H2 receptors are suitable candidates in clinical trials for the treatment of chronic pain conditions, such as IC-related pelvic pain.…”
mentioning
confidence: 99%